Biochar from Raw Materials Arundo Spp; Effect on Corn Plant Growth and Production - Iwar Barus,; Guna Darman,; Syahrullah,; Ambo Upe,; Tenri Sau, (Jurnal Online Pertanian Tropik, 2024)
Biochar is widely used for water and soil remediation due to its local availability and low production costs. However, its effectiveness depends on the physicochemical properties related to the raw material and pyrolysis temperature, as well as the environmental conditions where it is used. Additionally, biochar is susceptible to natural aging caused by changes in soil or sediment moisture, which can alter its redox properties and interactions with contaminants such as arsenic. Therefore, we are interested in conducting fundamental research on raw materials from grass types and their influence on the growth and production of QPM corn plants. In this research, we carried out laboratory content tests and field experiments. The treatments were: p0 control, p1 = 3 tons ha-1 biochar, p2 = 6 tons ha-1 biochar, p3 = 9 tons ha-1, p4 = 12 tons ha-1, p5 = 15 tons ha-1. The experimental results showed that the administration of biochar made from Arundo Spp. 12 tons Ha-1 can increase the effective growth and production of corn plants